Karakteristik Pemimpin Menurut 2 Timotius 2:22-25 dan Implementasinya Bagi Pemimpin Komsel Di Gereja Eben Haezer Community Church, Semarang - Tilaar, Bonny Bruce; Baskoro, Paulus Kunto; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2025)
The life characteristics of the cell group leader are very important for the church because if the life characteristics of the cell group leader are not good, it will have a negative impact on the spiritual growth of the cell group members being shepherded. But the problem is why it is difficult for South Seoul to develop, some even go dormant or actually die, it really depends on the leader of the South Seoul. Therefore, it is hoped that church leaders can provide new work to answer this problem so that the cell can continue to develop and even multiply, so that the church will become stronger. The method that will be used in writing this paper is a qualitative research method, with descriptive research stages using a library approach or literature study. The aim of this research is First, to find the characteristics of South Korean leaders according to 2 Timothy 2:22-25. Second, implementing the characteristics of leaders in the cell group at Eben Haezer Community Church, Semarang.